Network Pharmacology Approach to Acalypha indica L. and Plumbago zeylanica L. As Anti-Rheumatoid Arthritis Candidates - Dini Afriliza; Rina Herowati; Ana Indrayati (Universitas Airlangga, 2024)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease that can reduce quality of life. Currently, the goal of therapy is to achieve remission and prevent joint damage and disability. Acalypha indica L. and Plumbago zeylanica L. are known to be involved in rheumatoid pathogenesis. Objective: This study aimed to determine the compounds in Acalypha indica L. and Plumbago zeylanica L. that correlate with target proteins and anti-rheumatoid arthritis mechanisms. Methods: Plant compound data were collected from the KNApSAcK and IMPPAT databases, target protein data were collected using the KEGG pathway, validated using UniProt, and protein-protein interactions were analyzed using STRING. Target protein prediction using SwissTarget Prediction and SEA. Visualization of network pharmacology profiles using Cytoscape software based on the correlation between plant compounds and target proteins. Results: Acalypha indica L., which correlates with target proteins, contained quinine, gallotannin, 1,4 benzoquinone, chrysin, and kaempferol. For Plumbago zeylanica L., the compounds were vanillic acid, cinnamic acid, plumbagin, isoaffinetin, isoorientin, isovitexin, methylnaphthazarin, l-tryptophan, beta-sitosterol, stigmasterol, ficusin, suberosin, and quercetin 3-ol-rhamnoside. Conclusion: Network pharmacology visualization results showed that both Acalypha indica L. and Plumbago zeylanica L. correlated with disease target proteins in their respective rheumatoid arthritis signaling pathways.